2017
DOI: 10.1021/acsnano.7b04494
|View full text |Cite
|
Sign up to set email alerts
|

Large-Area Fabrication of Droplet Pancake Bouncing Surface and Control of Bouncing State

Abstract: Superhydrophobic pillar arrays, which can generate the droplet pancake bouncing phenomenon with reduced liquid-solid contact time, have huge application prospects in anti-icing of aircraft wings from freezing rain. However, the previously reported pillar arrays, suitable for obtaining pancake bouncing, have a diameter ≤100 μm and height-diameter ratio >10, which are difficult to fabricate over a large area. Here, we have systematically studied the influence of the dimension of the superhydrophobic pillar array… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(105 citation statements)
references
References 36 publications
4
100
0
1
Order By: Relevance
“…Superhydrophobic surfaces with tunable microstructures can overcomet he shortcomings of surfaces with static microstructures, for which the bouncing propertyi sc onstanta nd uncontrollable, and thus, are more attractive for complex intelligent devices.Agood example of this research is reported by Songe tal. [32] As showni n Figure 8a,h ierarchically structuredp illars with ad iameter, height, and spacingo fa bout1 .05, 0.8, and 0.25 mm, respectively,w ere prepared on the same substrate as that used in our work. [13] The SMP pillarsw ere easily pressed aslant for differenti nclination angles( a)u nder heatingc onditions.…”
Section: Droplet Bouncing Control On Superhydrophobic Smp Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Superhydrophobic surfaces with tunable microstructures can overcomet he shortcomings of surfaces with static microstructures, for which the bouncing propertyi sc onstanta nd uncontrollable, and thus, are more attractive for complex intelligent devices.Agood example of this research is reported by Songe tal. [32] As showni n Figure 8a,h ierarchically structuredp illars with ad iameter, height, and spacingo fa bout1 .05, 0.8, and 0.25 mm, respectively,w ere prepared on the same substrate as that used in our work. [13] The SMP pillarsw ere easily pressed aslant for differenti nclination angles( a)u nder heatingc onditions.…”
Section: Droplet Bouncing Control On Superhydrophobic Smp Surfacesmentioning
confidence: 99%
“…SEM images of SMP pillars with titling angles (a)o fabouta)90, b) 32, and c) 08.Inset:aschematic illustrationo fthe tilting pillars. d) Different bouncingp henomena for aw ater droplet on SMP pillars with different a. Reproduced with permission from ref [32]…”
mentioning
confidence: 99%
“…Droplet contact times were approximately threefold longer than the calculated theoretical time and significantly higher than synthetic surfaces that exhibit similar pancake bouncing behavior. 37 , 38 This extended droplet contact time is likely a function of the dynamic nature of the dragonfly wing surface which displays bending upon droplet impact. Dragonfly wings are flexible and are able to rapidly deform, allowing them to withstand stresses associated with flight.…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively, synthetic surfaces examined in previous droplet bouncing studies are typically flat or uniformly angled with limited or no flexibility in the macrostructure. 37 , 38 , 40 , 44 , 45 While we focused on the wing surface nanoarchitecture in this study, it is likely that interactions of macroscale features such as membrane corrugations, veins, and microtrichia contribute to the behavior of impacting water droplets. These findings warrant further work to understand more about this complex natural system.…”
Section: Discussionmentioning
confidence: 99%
“…On such surfaces water droplets are able to bounce, and the contact time between bouncing water droplets and superhydrophobic surfaces becomes a key factor of their dynamic characterization 7. The water bouncing motion is well studied by physicists and the contact time can be further reduced by tuning the surface micromorphology and droplet Weber number to achieve “nonaxisymmetric bouncing,”8 “pancake bouncing,”9 and “sausage bouncing”10 of water droplets.…”
Section: Introductionmentioning
confidence: 99%